2019
DOI: 10.1002/1873-3468.13620
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the movement of the amphipathic helix in the respiratory complex I using a nitrile infrared probe and SEIRAS

Abstract: Conformational movements play an important role in enzyme catalysis. Respiratory complex I, an L‐shaped enzyme, connects electron transfer from NADH to ubiquinone in its peripheral arm with proton translocation through its membrane arm by a coupling mechanism still under debate. The amphipathic helix across the membrane arm represents a unique structural feature. Here, we demonstrate a new way to study conformational changes by introducing a small and highly flexible nitrile infrared (IR) label to this helix t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The peak at 1390 cm –1 corresponds to the symmetric stretching mode of ν­(COO – ) of ANTA carboxylate groups. , As the final step before protein imobilization, Ni 2+ complexation with the NTA surface led to small changes in the spectrum (Figure A3) with the appearance of two bands at 1604 and 1402 cm –1 assigned to the asymmetric and symmetric stretching mode of the carboxylate groups of NTA that get deprotonated after complexation with Ni 2+ . These spectra correspond to the previously described immobilization process. ,, After immobilization of the GlcP Se protein, the characteristic amide I band appears at 1650 cm –1 (Figure S2 in the SI). This signal includes coordinates from the CO vibrational mode of the protein backbone.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The peak at 1390 cm –1 corresponds to the symmetric stretching mode of ν­(COO – ) of ANTA carboxylate groups. , As the final step before protein imobilization, Ni 2+ complexation with the NTA surface led to small changes in the spectrum (Figure A3) with the appearance of two bands at 1604 and 1402 cm –1 assigned to the asymmetric and symmetric stretching mode of the carboxylate groups of NTA that get deprotonated after complexation with Ni 2+ . These spectra correspond to the previously described immobilization process. ,, After immobilization of the GlcP Se protein, the characteristic amide I band appears at 1650 cm –1 (Figure S2 in the SI). This signal includes coordinates from the CO vibrational mode of the protein backbone.…”
Section: Resultssupporting
confidence: 68%
“…Before the protein immobilization, a thin gold layer was formed by chemical deposition on the surface of a silicon crystal as described previously. ,,,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steady-state experiments under continuous illumination were used to characterize νSCN spectral changes at different sites, and the variant with larger spectral changes, A44C–CN, was selected for time-resolved step-scan experiments extending from 10 μs to 18 ms . The incorporation of SCN probes by chemical modification of Cys residues has also been combined with studies at the monolayer level using SEIRAS . Two residues of the complex I of the respiratory chain were mutated to Cys and chemically modified.…”
Section: Tools For Band Assignmentmentioning
confidence: 99%
“…The variant was isolated from the mutant according to the protocol used for the preparation of the wild type and the inserted cysteine was decorated with a nitrile label. SEIRAS measurements (Santos Seica et al, 2020) with the labeled K161C CD variant showed that the IR absorbance of the label does not shift upon addition of NADH (Figures 3C and 3D). Interestingly, a clear movement of the IR signal was detectable in the presence of NADH plus Q, with the residue changing to a more hydrophilic environment (Figure 3D), indicating that the flexibility of the helix might be important to gain accessibility into the Q binding site.…”
Section: Structure Determinationmentioning
confidence: 95%